9. EVALUATE OF COMBINED METRONIDAZOLE PLUS IVERMECTINE EFFICACY IN THE TREATMENT FOR HUMAN DEMODICOSIS (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate of combined metronidazole plus ivermectine (MTZ + IVM) efficacy in treatment of human demodicosis.Methods: A non-randomized uncontrolled trial design for evaluate of combined MTZ + IVM regimen efficacy in treatment of human demodicosis.Results: The efficacy of combined MTZ + IVM regimen in the treatment for 80 enrolled demodicosis patients showed that significantly reduced of itching, stinging, crawling ants, and erythema/ red skin, and skin scales at points of before and after one and two months intervention; Demodex density reduced from 8.8±4.5 to 1.5 ± 1.1 and 0.6 ± 0.2/ microscope field after 1 and 2 months, respectively. The proportion of high response, moderate response, and low response were 80.3% and 88.7%; 13.2% and 5.6%; 3.9% and 1.4% in one and two months post-treatment, respectively. Non-response or treatment failure at one and two months post-treatment were 2.6% and 4.3%. Some advert events in the first ten days since drugs taken included of itching, skin burning 2 (2.5%), fatigue 6 (7.5%), dizziness 2 (2.5%), abdomen pain 3 (3.8%), nausea 3 (3.8%). Conclusions:Combined MTZ + IVM regimen has high efficacy 80.3% and 88,7% at one and two months post-treatment, respectively.
Keywords: Demodicosis; combined metronidazole ivermectine; efficacy